Comparing Optimal Portfolios: Markowitz vs. Single Index Models for IDX High Dividend 20 Stocks (2022) - Melati, Rampi; Risman, Asep (UPN Veteran Yogyakarta, 2024)
This study aims to implement portfolio models using the Markowitz Model and Single Index Model, and to qualitatively compare the portfolios formed by these two models. A quantitative descriptive approach is employed. The study focuses on a population of 24 companies listed in the IDX High Dividend 20 stock index for the year 2022. The optimal portfolio formation through the Single Index Model results in 5 candidate companies: ADRO (36.06%), BBCA (12.87%), BBNI (22.34%), BBRI (21.86%), ITMG (6.87%) with a return of 3.44% and a portfolio risk of 0.23%. Meanwhile, the Markowitz Model results in 6 candidate companies: ADRO (18.81%), BBCA (2.21%), INDF (20.25%), ITMG (12.75%), KLBF (40.82%), UNVR (4.86%) with a return of 2.89% and a portfolio risk of 0.10%.